Roles of the right dorsolateral prefrontal cortex during physical fatigue: a magnetoencephalographic study. Issue 3 (2nd July 2016) - Tanaka, Masaaki; Ishii, Akira; Watanabe, Yasuyoshi
ABSTRACT: Background: A regulation system in the central nervous system plays an important role in controlling physical performance during physical fatigue. Purpose: To clarify the neural mechanisms of this regulation system during physical fatigue using magnetoencephalography (MEG) and a classical conditioning technique. Methods: Eleven right-handed, healthy volunteers participated in this study. On the first experimental day, subjects performed fatigue-inducing maximum handgrips with their left hand for 10 min. Metronome sounds were started 5 min after beginning handgrip trials. The metronome sounds were used as conditioned stimuli and the maximum handgrip trials as unconditioned stimuli. The next day, subjects were randomly assigned to six groups in a single-blinded, three-crossover fashion to undergo three types of MEG recordings; that is, for control, inhibition, and facilitation sessions, while imagining maximum grip exercise by the left hand guided by the metronome sounds for 10 min. Results: Decreased oscillatory power for the alpha-frequency band (8–13 Hz) in the right dorsolateral prefrontal cortex (DLPFC) was observed during the facilitation session relative to the control session within 300–400 ms after the onset of handgrip cue sounds. In addition, increased oscillatory power for the alpha-frequency band was identified in the right DLPFC during the inhibition session relative to the control session within the time window of 400–500 ms. Conclusions: These results show that the right DLPFC is involved in the neural substrates of the regulation system during physical fatigue.